2017
DOI: 10.1021/acsami.7b09010
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally Functionalized Donor/Acceptor Homo- and Heterodimeric Dyes for Dye-Sensitized Solar Cells: An Approach to Introduce Panchromaticity and Control the Charge Recombination

Abstract: Organic dyes possessing conjugated π-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular π-π interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-D and D-D) and heterodimeric (D-D and D-D) donor/acceptor (D/A) dyes containing spiroBiProDOT π-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…After addition of 3 mM of CDCA the efficiency was increased up to 3.2 % with J sc of 7.5 mA/cm 2 and V oc of 0.635 V. Further, the IPCE profile of both D 1 ‐D sq , and the mixture of D sq ‐D sq , D 1 ‐D 1 and D sq , D 1 were looking almost with same features. Further, it has been observed that the V oc of dye mixture of D 1 ‐D 1 and D sq ‐D sq is 0.674 V, which is very close to the independent V oc of D 1 ‐D 1 (0.673 V) and 74 mV higher than that of D sq ‐D sq . Similar trends also have been observed for mixture of D 1 and D sq dyes.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…After addition of 3 mM of CDCA the efficiency was increased up to 3.2 % with J sc of 7.5 mA/cm 2 and V oc of 0.635 V. Further, the IPCE profile of both D 1 ‐D sq , and the mixture of D sq ‐D sq , D 1 ‐D 1 and D sq , D 1 were looking almost with same features. Further, it has been observed that the V oc of dye mixture of D 1 ‐D 1 and D sq ‐D sq is 0.674 V, which is very close to the independent V oc of D 1 ‐D 1 (0.673 V) and 74 mV higher than that of D sq ‐D sq . Similar trends also have been observed for mixture of D 1 and D sq dyes.…”
Section: Resultsmentioning
confidence: 52%
“…Solid‐state studies inferred that SpiroBiProDOT derivatives showed different conformations depending upon the substitution present in the moiety which helps to provide different orientation between the dyes that were functionalized with this spacer . Formylation of spiroBiProDOT under POCl 3 /DMF reaction conditions provided the corresponding dialdehyde 6 in good yield . The bromoindolium derivative 1 was condensed with the semisquaric acid 2 by azeotropic distillation of water employing a Dean−Stark apparatus to afford bromo‐functionalized squaraine precursor 3 in moderate yield(Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the corresponding non-spiro-linked parent compounds, spiro compounds have higher solubility, improved morphological stability in the solid-state and a reduced tendency to form aggregates [ 121 , 122 ]. The homodimeric spiro dye 32 showed higher PCE of 7.6% (see Table 1 ), which is 2.4 times the monomeric form, and the spiro linker offers the dye better flexibility [ 84 ].…”
Section: Dye Aggregation In Dsscsmentioning
confidence: 99%